Dendrimeric Antigens. New Approaches Towards Detection of IgE‐Mediated Drug Allergy Reactions - Montañez-Vega, María Isabel; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Ruiz-Sánchez, Antonio Jesús; Malkoch, M; Hult, A; Blanca, Miguel; Pérez-de-Inestrosa-Villatoro, Ezequiel (RSC Publishing, 2013)
Drugs are low molecular weight substances which cannot cause an immune response on their own. However, they can act as haptens and form covalent adducts with proteins. The resulting hapten‐carrier (drug‐protein) conjugate can induce an allergic reaction. Synthetic hapten‐carrier conjugates structurally comparable to those naturally formed in vivo, which in addition can be prepared in a control and reproducible manner, are often needed to diagnose drug allergy. The contribution of this chapter takes account of the structural precision and tunable properties of dendrimers for applications in the diagnosis of drug allergy. Dendrimers are often referred to as synthetic compounds able to mimic proteins in their interaction with the immune system. This success suggests dendrimers can be used for in vitro diagnosis of allergy, thus avoiding the use of invasive in vivo tests, which are usually considered as the standard in the diagnosis of hypersensitivity reactions. Different methodologies have been developed to prepare chemically controlled and reproducible dendronized and dendrimerized cellulose surfaces. These penicilloylated Dendrimeric Antigens interact with specific IgE antibodies meeting all the requirements in biosensor to detect penicillin allergy. Clinical evaluation of these materials shows that the use of a flexible spacer improves the IgE molecular recognition
Keywords: Antígenos; Dendrimeric antigens